Caracterización de las variantes del virus de bronquitis infecciosa que infectan los planteles avícolas de la Argentina y su relación con las vacunas comerciales - Geréz Miranda, Rocío del Carmen (2023)
Avian Infectious Bronchitis (IB) is a highly contagious disease of chickens that affects all productive categories in the poultry industry. The etiological agent is Infectious Bronchitis Virus (IBV), a member of the Coronaviridae family. IBV is a pleomorphic virus, with a positive-sense\nsingle-stranded RNA (+ssRNA) that codes for 4 structural proteins. The spike protein (S) is the\nmost important among them because its roles in i) attachment to the host cell; ii) tropism; and iii)\nimmunogenicity. The immune response is based on the production of neutralizing antibodies\ndirected against the antigenic determinants located on some domains of the subunit S1 of S\nprotein. Those domains are highly variable regions (HVR), which are poorly conserved among\nthe different strains, which is the cause of existence of a diversity of IBV variants with limited or no cross protection. The IBV variants can be characterized through virus neutralization essays by use of reference antisera, which allows to determine viral serotypes. In general, it is considered\nthat infection or vaccination against a serotype grants low to insignificant protection against a heterologous virus. The genomic area that encodes S1 was also used for genotyping. The\ngenotype characterization has shown that in Argentina two field variants belonging to the lineages GI-11 and GI-16 co-exist, being the latter the most prevalent. Until 2013, the IBV control in our\ncountry was based on two vaccine serotypes; Massachusetts (Mass) and Connecticut (Conn),\nsince then the 793/B serotype was added to the catalog of authorized vaccines. However, only\nrecently (and in our lab), we started to evaluate the antigenic similarities between field strains and\nvaccine serotypes.\nIn this thesis, we completed the antigenic characterization of A13 strain (GI-16 lineage),\ndetermining its relationship with the commercial vaccine?s serotypes. This achievement was\naccomplished by cross virus-neutralization (CVN) tests, performed first on chicken embryos (ChE)\nand after that on primary cell culture. For the latter, we adapted a chicken embryo kidney cell (ChEK) culture, which is less time and costs demanding when it is compared with ChE. Therefore, we determined that A13 (GI-16), CHu8 (GI-11), Ma5 (GI-1) and CR88 (GI-13) belong to different\nserotypes. That result strongly suggests that we need to review the IB control programs, considering the potential use of a vaccine strain that is homologous to the field variant (GI-16),\nwhich is currently not commercially available. Thus, it would be a remarkable contribution to the IB control in Argentina, if we had a vaccine belonging to GI-16 lineage. So, it becomes essential\nto obtain an attenuated strain of IBV (GI-16 lineage), that could be considered for vaccination.Accordingly, an attenuated A13 strain was obtained by serial passages in ChE, and its potential\nas vaccine candidate was evaluated afterwards. Those evaluations were based upon the use of\nthe following essays: i) safety trial (strain A13 was inoculated at high dose [109.624 EID50/ml]\nwithout disease signs or lesions appearance in the birds); ii) immunogenicity (strain A13 was inoculated at a lower dose [105 EID50/ml] inducing a proper antibody titer); iii) stability (no reversion after 4 serial infections by natural contact); and iv) vaccine efficiency against a challenge with a\nhomologous strain (compared with the protection given by vaccination with commercial vaccines of Massachusetts and 793/B serotypes). In order to perform the challenge trial, we developed (or\nadapted) and optimized techniques, which resulted of critical importance for the vaccine evaluation. They were: i) viral load quantitation in tracheal and kidney tissues (by real time RTPCR); and ii) a score system for ciliostasis evaluation (in tracheal tissue). On the other hand, in this thesis, we also performed a viral evolution study using as input the\nnucleotide sequences of some of the viral serial passages (on different biological supports) of IBV\nstrains. The aim was to analyze the nucleotide sequence of the viral genome in search of changes that can be associated with phenotypic modifications (e.g.: attenuation of virulence). The evolution study has shown that the nucleotides (and the encoded amino acids) changes occurred mostly in: ORF1 and S1. Unfortunately, we were unable to detect a pattern of nucleotide that allows us\nto associate it to changes in virulence or in viral adaptation to a particular host. In summary, in this thesis we have antigenically characterized the main field strain of IBV (GI-16)\naffecting the Argentinian poultry industry, determining the lack of relationship with the serotypes included in the commercial vaccines. Additionally, we obtained a vaccine candidate, homologous with the field variant, which accomplishes the safety standards, conferring a more efficient\nprotection than that provided by commercial vaccines